Valuing Outdoor Recreational Resources: A Case Study at Taman Negara, Pahang Darul Makmur - Mohd Salleh, Norlida Hanim (1999)
This case study estimated the demand for and value of the recreational resources in Taman Negara National Park, Pahang Darul Makmur. The two cardinal approaches used in this study were the Contingent Valuation Method (CVM) and Travel Cost Method (TCM). Since the benefit of non-market product is difficult to quantify, it is important to have proper and accurate evaluation techniques. The demand for outdoor recreation at Taman Negara National Park, is influenced by several factors. These include travel cost, income and socio-economic variables. The demand model in simple linear, semi-log and double log regression functional forms were estimated using the Ordinary Least Square (OLS) technique for Travel Cost Method; while the Logit and Probit techniques were used for the Contingent Valuation Method. The results show that only the average travel cost, the average on site cost and the average income influenced the demand for outdoor recreation in Taman Negara National Park. The economic value of outdoor recreation at the Taman Negara National Park was measured using the concept of user's willingness to pay in both Travel Cost Method and Contingent Valuation Method. The consumers' surplus for each individual was calculated to derive the economic values. The consumers' surplus of each individual for outdoor recreational resource at the Taman Negara National Park, using the Travel Cost Method was approximately RM123.60, calculated using the traditional approach and RM122.44 using the Gum-Martin approach. The Contingent Valuation Method yielded mean values of RM235.06 for the Logit technique and RM280.86 for the Probit technique.